2011
DOI: 10.3989/scimar.03669.21a
|View full text |Cite
|
Sign up to set email alerts
|

Benthic assemblages of rock pools in northern Portugal: seasonal and between-pool variability

Abstract: SUMMARY:We investigated the seasonal (winter vs summer and within season) and spatial (between-pool) variability of benthic assemblages of rock pools at mid-intertidal level along the shore of Viana do Castelo (North Portugal). Physical traits of rock pools, including size, depth and position along the shore, were also compared between pools. While pools did not differ for any of the examined physical traits, results indicated a clear seasonal difference in the structure of assemblages, including a total of 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Previous studies done in the study area have indicated that tidepool macroalgal assemblages show a seasonal pattern with significant differences between springesummer and autumnewinter periods (Rubal et al, 2011;Bertocci et al, 2012). To consider the spatial and temporal variability that macroalgal species experience in the study area, samples of the three target species (i.e.…”
Section: Sampling and Sample Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies done in the study area have indicated that tidepool macroalgal assemblages show a seasonal pattern with significant differences between springesummer and autumnewinter periods (Rubal et al, 2011;Bertocci et al, 2012). To consider the spatial and temporal variability that macroalgal species experience in the study area, samples of the three target species (i.e.…”
Section: Sampling and Sample Processingmentioning
confidence: 99%
“…In the studied shores, the composition of macroalgal assemblages has changed due to the introduction of non-native species over the past decades. Particularly, these shores have progressively been invaded by Sargassum muticum (Yendo) Fesholt, which nowadays is among the most common brown algae in the study area (Bertocci et al, 2012). Potential changes caused by the introduction of invasive macroalgae can be detected by alterations in the associated epifaunal assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…Data are estimated in situ using sub-quadrats (area, Dethier et al 1993, Parravicini et al 2010, Bertocci et al 2012 or point-quadrats (contact points, Foster et al 1991, Dethier et al 1993, Benedetti-Cecchi et al 1996. Data are obtained almost immediately but the results depend on the previous taxonomical knowledge of the diver.…”
Section: Introductionmentioning
confidence: 99%
“…These represented the habitat where Paracentrotus lividus was clearly more abundant and were hereafter indicated as 'rockpools' although some presented diffuse boundaries and could occasionally become exposed to air during period of extremely low tides and intense evaporation (Author observations). Temporal and spatial patterns of species composition in rockpool and emergent rocky habitats along the Portuguese coast were previously described (Araújo et al, 2006;Rubal et al, 2011;Bertocci et al, 2012a).…”
Section: The Study Systemmentioning
confidence: 99%
“…Thompson et al, 2002), rockpools can provide a particular habitat modulated by complex combinations of biological and physical factors in constant change between periods of low and high tides. Depending on their characteristics, they can provide different levels of protection against aerial exposure, extreme temperatures and irradiation (Metaxas and Scheibling, 1993;Schoch and Dethier, 1996;Martins et al, 2007) and regulate predation and competition (Lubchenco, 1982;Chapman, 1990), representing a determinant factor for the survival of a range of species (Clemente et al, 2013) and for the establishment of local assemblages highly variable in space and time (Benedetti-Cecchi and Cinelli, 1995;Thompson et al, 2002;Araújo et al, 2006;Rubal et al, 2011;Bertocci et al, 2012a). These complex patterns can be elucidated only by examining relevant ecological processes over a hierarchy of scales (e.g.…”
Section: Introductionmentioning
confidence: 99%